Credit allocation schemes: Perspectives from credit providers and regulatory regimes in Kenya - Samuel Tiriongo (Kenya Bankers Association (KBA), 2019)
This study analyses the credit channel of monetary policy transmission via major credit providers in Kenya before and during interest rate controls. Focusing on the period 2009M3- 2018m3 and employing a structural vector-autoregressive model, the study establishes whether controls on interest rates triggered a shift in credit allocation via a spectrum of providers; commercial banks, savings & credit cooperatives, and micro-finance banks. Findings show that the strength of policy signals in influencing credit allocation generally reduced, and the reductions varied from one provider to another. However, shares in total credit seem not to have changed substantially over time indicating no significant shifts in consumer preferences. A continued effort to review the interest rate capping rule is justified in improving overall credit allocation in the economy.
Keywords: C32; E51; E58; O11; 330; Credit channel; Monetary Policy Transmission; SVAR; Interest rate controls